ÈTUDE DE LA PROPAGATION DES HARMONIQUES DANS LES RÈSEAUX ÈLECTRIQUES - chaima Handel (My University, 2024)
The propagation of harmonics in electrical networks has become a major issue with the increasing integration of renewable energy sources and the presence of nonlinear loads. Renewable energy sources, such as photovoltaic systems, are often connected to the grid via inverters that can generate harmonics. These harmonics disrupt the ideal sinusoidal waveform of current and voltage, leading to energy quality problems. Nonlinear loads, such as rectifiers, exacerbate this situation by generating additional harmonic currents. In our thesis, we conducted numerical simulations in the MATLAB Simulink environment of a low voltage (LV) electrical network connected to photovoltaic (PV) energy sources with the presence of both fixed and variable nonlinear loads. We analyzed the waveform and harmonic spectrum of the current propagated to the electrical grid for each scenario, in order to propose adequate solutions to mitigate the effects of harmonics and improve the power quality. --------------------------------------------------------------------------------------------- أصبحت مشكلة انتشار التوافقيات في الشبكات الكهربائية قضية رئيسية مع زيادة تكامل مصادر الطاقة المتجددة ووجود الأحمال غير الخطية. تُوصَل مصادر الطاقة المتجددة، مثل الأنظمة الكهروضوئية، غالباً بالشبكة عبر محولات يمكن أن تولد التوافقيات. هذه التوافقيات تعطل شكل الموجة الجيبية المثالية للتيار والجهد، مما يؤدي إلى مشاكل في جودة الطاقة. تزيد الأحمال غير الخطية، مثل المقومات، من تفاقم هذه الحالة من خلال توليد تيارات توافقية إضافية. في رسالتنا، أجرينا محاكاة عددية في بيئة Matlab Simulink لشبكة كهربائية ذات جهد منخفض (LV) متصلة بمصادر الطاقة الكهروضوئية (PV) مع وجود أحمال غير خطية ثابتة ومتغيرة. قمنا بتحليل شكل الموجة وطيف التوافقيات للتيار المنتشر إلى الشبكة الكهربائية لكل سيناريو، بهدف اقتراح حلول مناسبة لتخفيف آثار التوافقيات وتحسين جودة الطاقة. ------------------------------------------------------------------------------------ La propagation des harmoniques dans les réseaux électriques devient un enjeu majeur avec l'intégration croissante des énergies renouvelables et la présence de charges non linéaires. Les sources d'énergie renouvelable, comme les systèmes photovoltaïques, sont souvent connectées au réseau via des onduleurs qui peuvent générer des harmoniques. Ces harmoniques perturbent la forme d'onde sinusoïdale idéale du courant et de la tension, entraînant des problèmes de qualité de l'énergie. Les charges non linéaires, telles que les redresseurs, aggravent cette situation en générant des courants harmoniques supplémentaires. Dans notre mémoire, nous avons réalisé des simulations numériques dans l'environnement Simulink de Matlab d'un réseau électrique basse tension (BT) connecté à des sources d'énergie photovoltaïque (PV) en présence de charges non linéaires fixes et variables. Nous avons analysé la forme d'onde et le spectre harmonique du courant propagé vers le réseau électrique pour chaque cas, afin de proposer, à la fin de cette étude, des solutions adéquates pour atténuer les effets des harmoniques et améliorer la qualité de l'énergie.